Estimativa e regionalização das vazões mínimas de referência para a Bacia do Rio Branco - RR, como suporte à gestão dos recursos hídricos - Ribeiro, Thiago Barboza (2018)
The granting of rights to use water resources, mentioned in the Water Resources National Policy (PNRH), aims to guarantee the quantitative and qualitative control of water. For an effective application of this management and regulation instrument, the water management state institution needs to determine the natural supply of the water resource to balance the demands among users, in a river basin, which is the management territorial unit. Considering that the knowledge of the minimum stream flows of reference is of great importance for the definition of the grantable water use limits of a basin, the purpose of this study was to estimate and regionalize the minimum stream flows of reference, Q7,10, Q95 and Q90 with annual and semi-annual frequency for the Rio Branco water basin, in Roraima State. Among the study the procedures used were: Historical series of flows and precipitation data for the basin, which occurred within the framework of the National Hydrometeorological Network (RHN); The definition of the hydrological year as well as the seasonal periods based on the hydrological data collected; The estimation of minimum reference stream flows under annual and semiannual studies; The regionalization of estimated minimum stream flows of reference; And finally, the impact evaluation of the semiannual seasonality of the minimum stream reference flows in granting for the water resources management in the basin. The minimum reference stream flows rates for thirteen fluviometric stations were estimated as well as the mean total rainfall was determined using 25 rainfall stations. In the other hand, for the study of regionalization of minimum reference flows, the identification of the Homogeneous Hydrological Regions (RHH) was carried out, and the regression between the minimum estimated flows (dependent variable) and the physical characteristics of the RHH, which were the area of drainage and total precipitation average (independent variables). Lastly, the regionalization equations for the identified RHH were defined. According to the results obtained, two RHH were identified for the Branco River basin, considering the results of the regressions. Significant increases in minimum stream flows of reference were observed when considering the rainy season in comparison to the annual one. As verified for the Caracaraí station, in the Branco river, where the adoption of the annual Q95 and Q90 inlet flows, replacing Q7,10, allows, respectively, an increase of 75.1% and 123.3% in the stream flow that could be granted. The results allowed to conclude that the estimation and regionalization of the minimum flows in the Branco river basin contribute to the analysis of the granting processes, since the water management state institution does not have established criteria for this purpose. This study provides information that allows the hydrological knowledge of the region as well as subsidize the decision making in the management of water resources, considering the instrument of granting the use of water resources. It was also concluded that the flexibility of the granting criteria adopting the water hydrological seasonality allows considerable increases in the grantable stream flows among the various users of the Branco river basin during the flood season.